Chemotherapy Compared with Radiotherapy as the First-line Therapy of Extranodal Marginal Zone Lymphoma: A Review - Mutmainah Mahyuddin; Karina Luthfia; Neni Anggraini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Objective: To compare the efficacy and safety between chemotherapy and radiotherapy as the main therapy of Extranodal Marginal Zone Lymphoma (EMZL). Method: Literature searching was conducted using PubMed, ScienceDirect, Google Scholar, ProQuest, and SpringerLink. All studies that met the inclusion and exclusion criteria were categorized based on the level of evidence. The data of demographic of the patients, staging of disease, type of treatments, and outcomes of this review including the number of local control rate, disease-free survival rate, overall survival rate, dosage, adverse drug reaction, complication and recurrence and/or relapses were also reported. Result: From ten article, both radiotherapy and chemotherapy as the first-line treatment have high complete remission rate. Local control (complete remission) of chemotherapy group ranged from 56,25%-93,9%, while in radiotherapy group ranged from 70%-100%. Overal survival rate ranged from 92%-100% for chemotherapy group and 90,4%-100% for radiotherapy group. The most complication of the radiotherapy group were cataract formation, while the chemotherapy group showed systemic complications (hematologic or non-hematologic). The most relapse cases were shown in radiotherapy group. Conclusion: Radiotherapy and chemotherapy showed high local control rates and survival outcomes especially in the early stages of extranodal marginal zone lymphoma (EMZL). Radiotherapy had a relatively higher incidence of ophthalmic complications that could interfere with patient’s quality of life. Therefore chemotherapy could be considered especially in younger patients.